Writing and colonialism in northern Ghana : the encounter between the LoDagaa and "The world on paper", 1892-1991 - Hawkins, Sean (Anthropological horizons., 2002)
Drawing on the work of a variety of other fields and disciplines - from the ancient Mediterranean to colonial Spain, and from anthropology to psychology - the author argues that colonialism in Africa needs to be understood through the medium of writing.